The real exchange rate and economic development - Arslan Razmi; Martin Rapetti; Peter Skott (University of Massachusetts, Department of Economics, 2011)
Recent empirical studies have found a robust correlation between competitive exchange rates and economic growth in developing economies. This paper presents (i) a formal model to help explain these findings and (ii) econometric evidence on the relation between investment and the real exchange rate. The model emphasizes the existence of (hidden) unemployment as a source of endogenous growth, even under constant returns to scale. Growth promoting policies, however, affect the external balance, and two instruments are needed in order to achieve targets for both the growth rate and the trade balance. The real exchange rate can serve as one of those instruments. The implications of the model for the relation between real exchange rates and the rate of capital accumulation find support in our econometric analysis.
Keywords: F43; O11; O41; 330; real exchange rates; underemployment; capital accumulation